The CX3C chemokine fractalkine in allergic asthma and rhinitis - Rimaniol, Anne-Cécile; Till, Stephen J.; Garcia, Gilles; Capel, Francis; Godot, Véronique; Balabanian, Karl; Durand-Gasselin, Ingrid; Varga, Eva Maria; Simonneau, Gerald; Emilie, Dominique; Durham, Stephen R.; Humbert, Marc (Journal of allergy and clinical immunology, 2003)
Unlike other chemokines, fractalkine is expressed as a membrane-bound form, mainly on endothelial and epithelial cells, and can be shed as a soluble chemotactic form. Fractalkine can capture leukocytes expressing its receptor (CX(3)CR(1)), including T lymphocytes, rapidly and firmly in an integrin-independent manner. Because of its dual activity, fractalkine plays a major role in the transendothelial and transepithelial migration of leukocytes during inflammation. We sought to study the fractalkine-CX(3)CR(1) axis in patients with allergic airways diseases. Plasma fractalkine levels were measured by means of ELISA in 19 control subjects and 55 patients with symptomatic allergic rhinitis, asthma, or both, and CX(3)CR(1) function was studied by using triple-color flow cytometry in circulating T-lymphocyte subpopulations. Segmental allergen challenge was performed in 16 allergic asthmatic patients to analyze fractalkine expression and inflammatory cell recruitment in bronchoalveolar lavage fluid and bronchial biopsy specimens. Compared with control subjects, patients with symptomatic allergic rhinitis and asthmatic patients had increased circulating fractalkine levels, and CX(3)CR(1) function was upregulated in circulating CD4(+) T lymphocytes. Twenty-four hours after segmental allergen challenge, bronchoalveolar lavage fluid soluble fractalkine concentrations increased and correlated with the total number of recruited cells. Bronchial epithelial and endothelial cells expressed high levels of the membrane-bound form of fractalkine before and after challenge. Allergic asthma and rhinitis are associated with systemic and bronchial upregulation of the chemotactic axis fractalkine-CX(3)CR(1). This might contribute to the rapid recruitment of circulating CD4(+) T lymphocytes in the airways after allergen stimulation.